Memorable Metaphor: How Different Elements of Visual Rhetoric Affect Resource Allocation and Memory for Advertisements. Issue 1 (2nd January 2017) - Peterson, Matthew; Wise, Kevin; Ren, Yilin; Wang, Zongyuan; Yao, Jiachen
ABSTRACT: This article explores how different uses of visual metaphor affect cognitive resource allocation and memory for pictorial advertisements. Metaphor is ubiquitous in advertising, and metaphors are often expressed entirely through imagery. Based on Phillips and McQuarrie's seminal typology of visual metaphor, we selected advertisements that featured either juxtaposition or fusion structures. We then conducted a within-subjects experiment in which thirty-six participants viewed a series of juxtaposition and fusion ads. While viewing each ad, participants were prompted to respond to a series of visual probes. Their reaction times to these probes served as an indicator of cognitive resource allocation. Afterward, we assessed participants' recognition and free recall accuracy. Reaction time data showed that fusion ads required greater cognitive resource allocation and yielded more accurate recall than juxtaposition ads. These results are discussed in terms of both theories of visual metaphor and limited capacity models of cognition.